Token Economy in Improving Discipline of Al-Quran Education Park Students - Cholili, Abd. Hamid; Mahbubi, M.; Azizaturrahmi, Rofiqo; Fadli, Nadia Alfiyyatus Sholihah; Wafa, Iqbal Ali (Bulletin of Counseling and Psychotherapy, 2025)
The Quran Education Park (TPQ) plays a vital role in accustoming children's behavior to become moral individuals with Koranic character and making the Al-Quran their guide for life. However, the results of field observations show that the discipline of students at TPQ is low. One way to foster discipline in children is by giving consequences as extrinsic reinforcement for their behavior; one form of reinforcement is the token economy. This research aims to determine the influence of the token economy on improving TPQ students' discipline. This research uses a quantitative approach with experimental research methods; the sample is 20 children, and data analysis uses the Paired Sample t-test technique. The results of the paired sample t-test are 0.000 < 0.05, which shows the significant influence of implementing the token economy in improving the disciplinary attitudes of TPQ students. Apart from that, there was an increase in the average score between the pre-test and post-test of 4.30.